Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Dalam Menginap Di Wisma Sartika Kota Lhokseumawe - T. Edyansyah; Juni Ahyar (Jurnal Visioner & Strategis, 2021)
The purpose of this study was to determine the effect of service quality consisting of reliability, responsiveness, assurance, empathy and physical evidence on customer satisfaction in staying at Wisma Sartika, Lhokseumawe City and to determine the effect of service quality simultaneously on customer satisfaction in staying at Wisma Sartika. Lhokseumawe City. The data collection techniques used are questionnaires and literature study. The author distributes questionnaires to 100 consumers who use lodging services at Wisma Sartika Lhokseumawe City. From the results of multiple linear regression analysis and partial test results, the responsiveness variable is the most dominant variable affecting customer satisfaction Simultaneous testing, reliability, responsiveness, assurance, empathy, physical evidence variables have a significant effect on customer satisfaction (in staying at the Wisma Sartika Lhokseumawe City, the value of the correlation coefficient (R) is 0.793 and the value of Adjusted R2 is 0.609 or 60.9% and the remaining 39.1% can be influenced by other variables not examined in this study.